The public option : how to expand freedom, increase opportunity, and promote equality - Sitaraman, Ganesh; Alstott, Anne, 1963- (Harvard University Press, 2019)
Whenever you go to your local public library, send mail via the post office, or visit Yosemite, you are taking advantage of a longstanding American tradition: the public option. Some of the most useful and beloved institutions in American life, from public schools to museums, are public options--yet they are seldom celebrated as such. These government-supported opportunities co-exist peaceably alongside private options, ensuring equal access and expanding opportunity for all. Ganesh Sitaraman and Anne Alstott challenge decades of received wisdom about the proper role of government, inviting us to look past the political red herrings peddled by the right (and sometimes the left) and consider the vast improvements that could come from the expansion of public options. Far from illustrating the impossibility of effective government services, as their critics claim, public options hold the potential to transform American civic life, offering a wealth of solutions to seemingly intractable problems, from housing shortages to the escalating cost of health care. Imagine a low-cost, high-quality public option for child care. Or an extension of the excellent Thrift Savings Plan from federal employees to all Americans. Or every person having access to a bank account at the Fed, with no fees and no minimums. From broadband internet to higher education, The Public Option reveals smart new ways to meet pressing public needs while spurring healthy competition. More effective than vouchers or tax credits, and far more equitable than blind faith in the marketplace, public options could offer us all fairer choices, greater security, and more meaningful participation in American life.--